Assessment of Health Problems Contributed to Life Style Behaviour in Secondary School Student in Mosul City - Abdul Kareem Ghanim Abdul Aziz; Kahtan Hadi Hussein (College of Nursing,University of Mosul, 2016)
Background and aim: Adolescents form two-thirds of our population. This is a unique group of People with special needs. The study aims to assess lifestyle behaviors of secondary school students through the domains of physical activity, sedentary lifestyle, smoking, personal hygiene e.g. tooth brushing), to look for the presence a relationship between health problem and lifestyle behaviors of secondary school students, to assess the relationships between lifestyle behaviors and health problems of secondary school students and sociodemographic characteristics. Materials and method: A cross- sectional descriptive study conducted in Mosul City from13 October 2013 to 31 March 2014. A stratified- cluster sample of 1656 students (828 males and 828 females) whose age between 15- 19 years were selected. The schools selected randomly are 24 schools from 76 total schools in Mosul City. Data are collected through the use of semi-constructed questionnaire. Results: The results of the present study demonstrated that there is non-significant relationship between students and family socio-demographic characteristic (age, sex, class level, student's order in the family and family income) while there is significant relationship between students and family socio-demographic characteristics ( residence, number of siblings and family type), also a highly significant relationship was shown between weight with age and sex. Conclusions: The study confirms that 13.7% of students are obese and 12.9% of students have simple hypertension. Physical inactivity and sedentary leisure behavior are most common among students. Recommendations: The researcher recommends promoting school health programs, family and community involvement to help these students live a healthier life, using mass media, which play an important role to identify healthy lifestyle behaviors and establishing national policy between Ministry of Health and Ministry of Education to promote healthier lifestyle behaviors for adolescents. Keywords: Lifestyle, health problem, behavior, contributed.